2016
DOI: 10.1186/s13017-015-0060-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the results of laparoscopic appendectomies with application of different techniques for closure of the appendicular stump

Abstract: BackgroundNowadays laparoscopy is used frequently not only in elective surgery but also in abdominal emergencies, including acute appendicitis. There are several techniques used to close the appendicular stump during laparoscopic appendectomy. The aim of the study was to present and compare the results of minimally invasive appendectomies performed with the use of endoscopic staplers (group A), titanium endoclips (group B) and invaginating sutures (group C).MethodsThree hundred seven patients (mean age = 35.6;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 19 publications
2
18
0
1
Order By: Relevance
“…In several studies the duration of surgery and mean duration of hospital stay for closure of appendicular stump in laparoscopic appendicectomy was between 45-60 minutes and 1-7 days respectively, current data correlate well with these studies. 13,23 In present study, the complication rates observed correlate well with similar studies. 13,23,24 According to recent studies the lack of evidence of superiority of the technique the surgeon should choose suitable technique for him as well as the patient.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In several studies the duration of surgery and mean duration of hospital stay for closure of appendicular stump in laparoscopic appendicectomy was between 45-60 minutes and 1-7 days respectively, current data correlate well with these studies. 13,23 In present study, the complication rates observed correlate well with similar studies. 13,23,24 According to recent studies the lack of evidence of superiority of the technique the surgeon should choose suitable technique for him as well as the patient.…”
Section: Discussionsupporting
confidence: 91%
“…13,23 In present study, the complication rates observed correlate well with similar studies. 13,23,24 According to recent studies the lack of evidence of superiority of the technique the surgeon should choose suitable technique for him as well as the patient. 13 The optimum technique should have safety and least complication rate and should be cost effective.…”
Section: Discussionsupporting
confidence: 91%
“…But, it has some disadvantages, such as longer duration of operation, increased cost and more incidence of intraabdominal abscess (2,5,11).…”
Section: Introductionmentioning
confidence: 99%
“…Advantages of LA, include, shorter hospitalization, faster recovery, less postoperative pain, less analgesic necessity, less surgical site infection and better cosmetic results (2,3,5,(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation